Bāṃlādeśera ālokita Musalima mānasa - Rāihāna, Ābu (Eḍukeśana Phorāma, 2022)
Critical articles chiefly on Bengali literature contributed by 20th century Muslim authors from Bangladesh.
Keywords: Aufsatzsammlung; Bengali literature; 20th century; History and criticism.; Bengali literature; Muslim authors; History and criticism.; Islam in literature.